Practical procedures for subjective testing (International Telecommunication Union, 2011)
This Handbook describes practical procedures to be used to quantify the perceived audio quality of end-to-end speech and audio communication systems. These procedures may be used, for example: * for designing and implementing subjective tests to qualify, select, characterize, or verify the performance of speech codecs and other network signal processing equipment, * for providing information for planning and objective assessment tools. Audiovisual subjective test procedures as described in the ITU-T P. 900-series of Recommendations are outside the scope of this Handbook. The contents of this Handbook are also provided to assist speech and audio quality experts to set up subjective testing laboratories equipped with adequate tools and devices to run subjective experiments. The goal is to achieve, via listening or conversational tests, valuable results to classify existing and/or new speech coding algorithms or determine the end-to-end quality of complete communication systems, from the point-of-view of subjectively perceived quality or degradation.